An Investigation on the Effects of a Zinc Complex on Goose Genomic DNA - Kadir Devrim, A.; Arslantas, Ali; Kaya, Necati; Necefoglu, Hacali (Asian Journal of Chemistry, 2010)
A zinc complex with p-aminobenzoate [Zn(p-H2NC6H4 COO)2(H2O)4]n·1.5nH2O has been synthesized. The interaction of the complex with genomic DNA was investigated by viscosity measurements and spectrometric methods. The experimental results indicated that complex bound to DNA by intercalative mode via the ligand. In this study, DNA breaking activity of the compound have also been examined through an agarose gel electrophoresis experiment using genomic DNA. The result showed that no DNA breakings took place. The electrophoretic mobility of the bands was observed to decrease slightly as the concentrations of ZnPAB were increased from 0.065 to 0.65 and 65 mM. The change in mobility could be due to a change in conformation of the DNA.